Drug Utilization 90% Profile of Antibiotics Use during the Period of 2013 – 2017 at a Private Teaching Hospital in Yogyakarta - Saepudin Saepudin; Cinthia Sendysagita; Endang Yuniarti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2022)
Evaluation of antibiotics use plays an important role in antimicrobial stewardship programs to support the rational use of antibiotics at all healthcare facilities. This study aimed to describe the profile of drug utilization 90% (DU90%) of antibiotics use for hospitalized patients at a private teaching hospital in Yogyakarta over period of 2013 – 2017. Aggregate data of all systemic antibiotics having an anatomic therapeutic chemical (ATC) code and used for hospitalized patients during 2013 – 2017 were included in this study. Quantity of antibiotics use was expressed in defined daily dose (DDD) and final quantity was expressed in DDD/100 bed days. DU90% profile was obtained by calculating the cumulative use of antibiotics from the highest to the lowest percentage. There were 44 antibiotic agents used each year over the period of 2013 – 2017. However, there were only 10 – 12 agents within the DU90% segment. Cephalosporins group was identified as the most used antibiotics consistently over the period and the top three antibiotics that were consistently prescribed were: ceftriaxone, levofloxacin, and cefixime. It can be concluded that only about a quarter of the total antibiotic agents used in hospitals are within the DU90% segment and those antibiotic agents are relatively consistent, especially for the top three of the highest used antibiotics.